2D and 3D Ultrasonographic Evaluation of Fetal Midface Hypoplasia in Two Cases with 3-M Syndrome - Vimercati, A.; Chincoli, A.; de Gennaro, A. C.; DʼAddario, V.; Cicinelli, E. (Geburtshilfe und Frauenheilkunde, 2016)
This paper highlights the utility of 2D and 3D ultrasonography in the prenatal diagnosis of facial dysmorphisms suggestive of very rare syndromes such as 3-M syndrome. Two pregnant women at risk for fetal skeletal dysplasias were referred to our clinic for 2D/3D ultrasound scan in the second trimester of pregnancy. Only one of the patients had a familial history of 3-M syndrome. Karyotyping and genetic testing of abortion material were performed in both cases. 2D ultrasonography revealed growth retardation of the long bones in both cases. In the case without a familial history of the syndrome, 2D and 3D ultrasonography showed an absence of nasal bones and a flat malar region suggestive of 3-M syndrome, although the difficult differential diagnosis included other dysmorphic growth disorders with prenatal onset. The karyotype was normal but the pregnancy was terminated in both cases. Postmortem examination confirmed 3-M syndrome as indicated by prenatal findings. In high-risk cases with a familial history of 3-M syndrome, prenatal diagnosis of 3-M syndrome is possible by analyzing fetal DNA. In the absence of risk, a definitive prenatal diagnosis is often not possible but may be suspected in the presence of shortened long bones, normal head size and typical flattened malar region (midface hypoplasia) shown on complementary 2D and 3D sonograms. 2D and 3D ultrasonography has been shown to offer reliable information for the prenatal study of skeletal and facial anomalies and can be useful if there is a suspicion of 3-M syndrome in a pregnancy not known to be at risk.
Keywords: fetal midface hypoplasia; 3-M syndrome; prenatal diagnosis; ultrasound